Flavin Adenine Dinucleotide and N5, N10‐Methenyltetrahydrofolate are the in planta Cofactors of Arabidopsis thaliana Cryptochrome 31. (7th September 2016) - Göbel, Tanja; Reisbacher, Stefan; Batschauer, Alfred; Pokorny, Richard
Abstract: Members of the cryptochrome/photolyase family (CPF) of proteins utilize noncovalently bound light‐absorbing cofactors for their biological function. Usually, the identity of these cofactors is determined after expression in heterologous systems leaving the question unanswered whether these cofactors are identical to the indigenous ones. Here, cryptochrome 3 from Arabidopsis thaliana was expressed as a fusion with the green fluorescent protein in Arabidopsis plants. Besides the confirmation of the earlier report of its localization in chloroplasts, our data indicate that fractions of the fusion protein are present in the stroma and associated with thylakoids, respectively. Furthermore, it is shown that the fusion protein expressed in planta contains the same cofactors as the His6 ‐tagged protein expressed in Escherichia coli, that is, flavin adenine dinucleotide and N 5, N 10 ‐methenyltetrahydrofolate. This demonstrates that the heterologously expressed cryptochrome 3, characterized in a number of previous studies, is a valid surrogate of the corresponding protein expressed in plants. To our knowledge, this is also a first conclusive analysis of cofactors bound to an Arabidopsis protein belonging to the CPF and purified from plant tissue. Abstract : Cryptochrome 3 (cry3) of Arabidopsis thaliana was expressed as a fusion with green fluorescent protein (GFP) in plants and was detected in the total extract of mature rosette leaves as well as within and outside the membrane fraction of the isolated chloroplasts. The fusion protein was immunoprecipitated from the total extract by a single‐domain antibody fragment against GFP linked to magnetic beads. After protein denaturation, flavin adenine dinucleotide and N 5, N 10 ‐methenyltetrahydrofolylpolyglutamate were identified as cofactors of cry3‐GFP expressed in A. thaliana in agreement with the well‐characterized version of cry3 expressed in Escherichia coli .